2013
DOI: 10.1111/1348-0421.12095
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity by oral immunization with heat‐killed Shigella strains in a guinea pig colitis model

Abstract: The protective efficacy of and immune response to heat-killed cells of monovalent and hexavalent mixtures of six serogroups/serotypes of Shigella strains (Shigella dysenteriae 1, Shigella flexneri 2a, S. flexneri 3a, S. flexneri 6, Shigella boydii 4, and Shigella sonnei) were examined in a guinea pig colitis model. A monovalent or hexavalent mixture containing 1 Â 10 7 of each serogroup/serotype of heatkilled Shigella cells was administered orally on Days 0, 7, 14 and 21. On Day 28, the immunized animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…The current study confirmed the efficacy of the heat‐killed hexavalent Shigella vaccine , by investigating protective immunity in an infant mouse model wherein the offspring of immunized dams were challenged by wild strains of Shigellae. The level of protection was measured as the degree of colonization of the challenged bacteria in the bowel .…”
Section: No Of Colonized Challenge Bacteria In the Bowel Of Shigellasupporting
confidence: 61%
See 1 more Smart Citation
“…The current study confirmed the efficacy of the heat‐killed hexavalent Shigella vaccine , by investigating protective immunity in an infant mouse model wherein the offspring of immunized dams were challenged by wild strains of Shigellae. The level of protection was measured as the degree of colonization of the challenged bacteria in the bowel .…”
Section: No Of Colonized Challenge Bacteria In the Bowel Of Shigellasupporting
confidence: 61%
“…To develop a vaccine that confers broad‐spectrum coverage requires the inclusion of all epidemic and endemic Shigella serotypes . Recently, we reported that an oral vaccine candidate of heat‐killed Shigella strains ( S. dysenteriae 1, S. flexneri 2a, S. flexneri 3a, S. flexneri 6, S. boydii 4, and S. sonnei ) achieved significant levels of protection against shigellosis in a guinea pig colitis model . Similarly, Kaminski et al reported the successful development of a trivalent, formalin‐inactivated Shigella whole‐cell vaccine.…”
Section: No Of Colonized Challenge Bacteria In the Bowel Of Shigellamentioning
confidence: 90%
“…The serum titers of IgG and IgA against lipopolysaccharide of each of the six Shigella serogroups/serotypes increased. These data indicate that a hexavalent mixture of heat-killed cells of the six Shigella serogroups/serotypes tested would be a possible broad-spectrum candidate vaccine against shigellosis Barman et al, 2013 . In an oral immunization trial on two-month-old guinea pigs, the heat-killed cell suspension of monovalent or Roszak and Colwell, 1987 . Existence of viable but nonculturable VBNC V. cholerae is the one reasonable explanation for the difficulty of isolation of viable cells of the vibrio from the environmental water samples.…”
Section: Fig 2bmentioning
confidence: 95%
“…With these points in mind, we have formulated a heat-killed hexavalent prototype vaccine from a combination of six Shigella strains: S. dysenteriae 1 (NT4907 stx), S. flexneri 2a (B294), S. flexneri 3a (C519), S. flexneri 6 (C347), S. sonnei (IDH00968) and S. boydii 4 (BCH612). Our recent laboratory study showed that these newly formulated hexavalent immunogens successfully induce a homologous protective response in guinea-pig rectocolitis model (Barman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%